A origem histórica da Associação dos Docentes da Universidade de Brasília (ADUNB) – 1978-1982 - Maier, Thabata Lea (2024)
This research addresses the trajectory of the Association of Teachers of the University of Brasília (ADUnB) in the period from 1978 to 1982. Since its foundation on May 24, 1978, the entity has always been committed to defending the interests of teachers and promoting teaching public, free, secular and quality for everyone. His performance was marked by moments of great political and social adversity, including resistance to the civil-military dictatorship. The research is justified by discussing the social and political context in which professors from the University of Brasília (UnB) founded ADUnB. We start from the following research assumption: what were the relationships, articulations and impacts of the teaching movement at the University of Brasília. Who are the protagonists whose actions and collaborations revolve around the mobilization for the founding of ADUnB. What strategies and alliances were used by UnB professors. How the social, historical and political context influenced the conditions that allowed the emergence of associations and teaching unionism at UnB. The methodology is structured on literature review and bibliographical survey, the empirical basis was based on oral sources such as semi-structured interviews, photographs, newspapers from the mainstream press, bulletins, posters, minutes and other printed and written documents that can collaborate with us in rescuing memory of its creators and in the critical construction of the history of ADUnB. As a result of the research, it is highlighted that ADUnB promoted significant advances during its four years of operation at the University of Brasília. Gradually, teachers managed to gain rights that had been repressed by the dictatorship, which imposed authoritarianism on the university campus. Furthermore, ADUnB played an important role in overcoming oligarchic management that limited the participation of the academic community in UnB's decision-making processes.